Second International Workshop on Variability Modelling of Software-intensive Systems. Proceedings - Patrick Heymans; Kyo-chul Kang; Andreas Metzger; Klaus Pohl (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2008)
This ICB Research Report constitutes the proceedings of the Second International Workshop on Variability Modelling of Software-intensive Systems (VaMoS'08), which was held from January 16-18, 2008 at the University of Duisburg-Essen.
Keywords: 650; Softwareindustrie; Betriebliches Informationssystem